ВИЗНАЧЕННЯ УМОВ ЗМЕНШЕННЯ ЕНЕРГОНАКОПИЧЕННЯ У ВИХІДНИХ КОЛАХ ДЖЕРЕЛ ЕЛЕКТРОЖИВЛЕННЯ ПОТУЖНИХ ГАЗОРОЗРЯДНИХ УСТАНОВОК - Мартинов, В.В. (Інститут електродинаміки НАН України, Київ, 2023)
The energy intensity of the output circuit of a high-voltage pulse source for a gas-discharge load is determined by the totality of energies accumulated in its reactive elements in operating or transient modes. During breakdowns in the output circuit of high-voltage power supplies, the accumulated energy can be released uncontrollably and lead to element failures or technological defects. The relationship between the magnitude of the output voltage ripple, the load resistance, the parameters of the inductive-capacitive output filter, the power of the power source and the frequency of its conversion has been established. Analytical expressions are obtained that make it possible to calculate the parameters of the output filter of a high-voltage powerful power supply based on the allowable energy that can accumulate in the output filter while providing allowable voltage ripples at the output of the converter. It has been established that the lower the attenuation coefficient of transient processes, the more energy must be accumulated in the filter elements to ensure the required quality of the output energy. On a calculated example of a power supply with a voltage of 30 kV, a power of 450 kW, a conversion frequency of 20 kHz and output ripples of less than 1%, it is shown that for implementation without oscillatory transients with significant changes in load current, the energy intensity of the output filter can exceed 1 J/kW. With an increase in the equivalent conversion frequency, this indicator can be significantly reduced. References 13, figures 4.